Spatiotemporal characteristics of hourly precipitation over central eastern China during the warm season of 1982–2012. (29th November 2015) - Li, Deshuai; Sun, Jianhua; Fu, Shenming; Wei, Jie; Wang, Shigong; Tian, Fuyou
ABSTRACT: An intensive observational hourly precipitation data set from the China Meteorological Administration was utilized to investigate the changes in precipitation amount, frequency, intensity and duration over central eastern China during the warm season from 1982 to 2012. Ten intensity categories were used to reveal the contributions of precipitation frequency and intensity to the variation of rainfall amount. Moreover, the trends of frequency were also evaluated by comparing the respective contributions of the number and the duration of precipitation events. The main results are as follows: (1) The precipitation amount and intensity both decreased from southeast to northwest China, with two areas of high precipitation frequency located in southwestern and southeastern China. A region of high precipitation duration was found in central China and two lower duration regions were found in southern and northern China. (2) Generally, the extreme heavy rainfall showed a significant increasing trend while the light rainfall showed a significant decreasing trend over central eastern China. Nevertheless, the spatial unevenness was detected and in south and southeast China, significant increasing trends were found, whereas in northeast China and the Sichuan Basin, precipitation amounts showed a declining trend in each precipitation intensity category. (3) The trends of precipitation amount were mainly caused by the variations of precipitation frequency, which had a contribution rate of greater than 95%; however, for the heavy rainfall category, intensity changes were also very important. (4) Increased precipitation frequency was largely caused by the prolonged duration of rainfall events, whereas the decreased frequency was mainly due to the reduction in the number of rainfall events.